PENERAPAN PERLINDUNGAN HAK KONSUMEN TERHADAP PEMAKAI PRODUK VAPOR LIQUID DILAKUKAN OLEH PENJUAL VAPOR LIQUID - Sagala, Alberto Syahputra; Firdaus, Firdaus; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Protection of consumers requires that there be partiality to the weak(consumers). Every decision concerning the interests of the lives of many peoplemust be oriented towards the public interest. The desire to be achieved inprotecting consumers is to create a sense of security for consumers in fulfillingtheir daily needs. In short, all efforts intended to protect consumers are not onlypreventive measures, but also repressive actions in all areas of protection given toconsumers. One of the rights is the right to correct, clear and honest informationabout the condition and guarantee of goods and / or services.Products circulating in the community that do not comply with LawNumber 8 of 1999 concerning Consumer Protection. Especially for Article 4 (c),Article 8 (i) and (j), namely about product information. Vapor liquid (ElectricCigarette) is a product that has no information and is based on data that isprocessed, Liquid ingredients are very dangerous for Humans.The Ministry of Health of the Republic of Indonesia publishes the dangersof e-cigarettes, that Electronic Cigarettes (Ecs) or Electronic Nicotine DeliverySystem (ENDS) are devices that function to convert chemicals into steam anddrain them into the lungs, where they are a mixture of substances such as nicotineand propylene glicoli. ECS / ENDS consists of evaporator components,rechargeable batteries, electronic regulators and liquid containers that will beevaporated. Until now, the safety of ENDS has not been proven to be scientificallysafe, because it is suspected that these substances contain dangerous substancessuch as nicotine and high concentrations of propylene glycol, which is an irritantthat is inhaled. Based on tests by the Food and Drug Administration (FDA), someproducts also contain diethylene glycol, which is a chemical used to poison.The purpose of this thesis is: First, to find out whether the sales of vaporliquids made by business actors are in accordance with the applicableregulations, Secondly, to find out how the efforts of businesses in protecting theconsumer rights of vapor liquidThis type of research is sociological research orresearch that wants to see the correlation between society and law. The results ofthis study are two points concluded. First, sales of vapor liquids in accordancewith applicable regulations. Second, the efforts made by business actors inprotecting consumer rights.Keywords: Consumer rights - Liquid -Vapor information - Legal efforts